1974
DOI: 10.2307/1442530
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of the Bonnethead Shark, Sphyrna tiburo

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Society of Ichthyologists and Herpetologists (ASIH)is collaborating with JSTOR to digitize, preserve and extend access to Copeia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
119
3

Year Published

1990
1990
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 16 publications
14
119
3
Order By: Relevance
“…After parturition, juvenile lemon sharks display high site fidelity in their first few years of life (Morrissey & Gruber 1993, Franks 2007, suggesting that social encounters between related individuals are highly probable. Finally, in accordance with previous studies on dominance hierarchies in captive sharks, we predicted that larger juvenile lemon sharks would lead groups more often than smaller conspecifics (Myrberg & Gruber 1974, Brown 2004.…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…After parturition, juvenile lemon sharks display high site fidelity in their first few years of life (Morrissey & Gruber 1993, Franks 2007, suggesting that social encounters between related individuals are highly probable. Finally, in accordance with previous studies on dominance hierarchies in captive sharks, we predicted that larger juvenile lemon sharks would lead groups more often than smaller conspecifics (Myrberg & Gruber 1974, Brown 2004.…”
Section: Introductionsupporting
confidence: 90%
“…1b) for several years and recognized it as an aggregation site for juvenile lemon sharks with as many as 25 individuals using the site at high tide (water depth: 0.2 to 0.9 m). When systematically observed, we found that they spent their time performing group behaviours, such as follow, circle or parallel (Myrberg & Gruber 1974). When not in groups, solitary sharks were observed to patrol the area, neither feeding nor interacting agonistically with each other (Guttridge 2009).…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations